Optimization Of Fermentation Culture Conditions For Alkaline Protease Production By Scopulariopsis Spp. (Applied Biological Research, 2013)
The present study was aimed to assess alkaline protease production by a locally  isolated soil fungus Scopulariopsis spp. The factors influencing enzyme  production were optimized under submerged conditions. Maximum enzyme  production occurred on 5th day of incubation on fermentation medium with  initial pH 9.0, incubation temperature 37ºC, inoculum concentration 3%, casein  2% as substrate and 1.5% tryptone as nitrogen source. Under these optimized  conditions, about 3-fold increase in protease activity (from 5.85 to 17.77 U ml-1)  was noticed. High enzyme activity at alkaline pH suggested that the fungus can  be exploited for use in leather processing and detergent industries.
Keywords: Alkaline protease; casein; optimization; Scopulariopsis; submerged fermentation